Effect of Static Cold Storage on Skeletal Muscle after Vascularized Composite Tissue Allotransplantation - Gok, Emre; Kubiak, Carrie A.; Guy, Erin; Kemp, Stephen W.P.; Ozer, Kagan (Journal of Reconstructive Microsurgery, 2020)
Background Prolonged cold ischemia associated with static cold storage (SCS) results in higher incidence of acute and chronic allograft rejection in solid organ transplantations. Deleterious effects of SCS on vascularized composite tissue allograft were studied with limited data on muscle structure and function. The aim of this study is to evaluate the long-term impact of SCS on muscle metabolism, structure, and force generation using a syngeneic rat hindlimb transplantation model.Methods Sixty-five male Lewis rats (250 ± 25 g) were distributed into five groups, including naive control, sciatic nerve denervation/repair, immediate transplantation, transplantation following static warm storage for 6 hours at room temperature, and transplantation following SCS for 6 hours at 4°C. Sciatic nerves were repaired in all transplantations. Muscle samples were taken for histology and metabolomics analysis following electromyography and muscle force measurements at 12 weeks after transplantation.Results All cold-preserved limbs remained viable at 12 weeks, whereas animals receiving limbs preserved in room temperature had no survivors. The SCS transplantation group showed a 73% injury score, significantly higher than groups receiving immediate transplants without cold preservation (50%, p < 0.05). A significant decline in muscle contractile force was also demonstrated in comparison to the immediate transplantation group (p < 0.05). In the SCS group, muscle energy reserves remained relatively well preserved in surviving fibers.Conclusion SCS extends allograft survival but fails to preserve muscle structure and force.
Keywords: static cold storage; VCA transplantation; muscle